HUBUNGAN MOTIVASI BELAJAR KEJURUAN DAN PERHATIAN ORANGTUA DENGAN PRESTASI BELAJAR MATA PELAJARAN KELISTRIKAN OTOMOTIF SISWA KELAS XI SMK AL GHAZALI MIRIT KEBUMEN TAHUN AJARAN 2015/2016 - Nopri Jumianto; Tarto Sentono (Universitas Sarjanawiyata Tamansiswa, 2016)
The study aimed to describe (1) correlation between vocational learning motivation with learning achivement of automotive electrical subject; (2) correlation between parents’ attention with learning achivement of automotive electrical subject of welding subject; and (3) correlation between vocational learning motivation and parents’ attention with learning achivement of automotive electrical subject. This study was ex-post facto research. Data collecting methods were questionnaires and documentation. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used double regression. This study shows that (1) there was a positive and significant correlation between vocational learning motivation with learning achievement with the significant score 0.022 < 0.05; (2) there was a positive and significant correlation between parents’ attention with learning achivement of automotive electrical subject with the significant score 0.014 < 0.05; and (3) there was a positive and significant correlation between vocational learning motivation and parents’ attention with learning achivement of automotive electrical subject with the significant score 0.002 < 0.05. The score of determinant coefficient (R2) 0.237, it means that vocational learning motivation and parents’ attention gave a positive contribution 23.7% toward learning achivement of automotive electrical subject, while 76.3% was influenced by other factors that were not discussed in this study.